Meningkatkan Keterampilan Menulis Puisi Menggunakan Media Gambar di Kelas III SD Negeri 106448 Bagan Serdang: Bahasa Indonesia - Syarifah Ainun Harahap (Medan Resource Center, 2022)
This study aims to determine the improvement of poetry writing skills using picture media in third grade students of State Elementary School 106448 Bagan Serdang for 2020/2021 Academic Year.The type of this study used is Classroom Action Research (CAR). In this study, researchers are involved or collaborate in learning activities. The researcher used the action research model of Kemmis and Taggart. This research was conducted in two cycles which included planning, implementation, observation and reflection activities. The subjects in this study were third grade students of State Elementary School 106448 Bagan Serdang, totaling 35 students. The instruments used are observation and tests. Observation data were analyzed by descriptive qualitative while the test results were analyzed by descriptive quantitative percentages.The results showed that the poetry writing skills of third grade students of State Elementary School 106448 Bagan Serdang using picture media had increased. This is evidenced by the increase in the percentage of students' writing skills test results in the pre-cycle with a percentage of 2.9% increasing to 68.6% in the first cycle and increasing in the second cycle to 97.1%.